(untitled) (Research, Society and Development, 2023)
Objective: Approach the manifestations and possible causes of dysfunctions of the temporomandibular joint, which can cause displacement of the mandibular condyle and cause dislocation of the temporomandibular joint. Methodology: This study comprises a narrative review that was developed with the aim of aligning knowledge about temporomandibular joint dislocation and its prevention methods so that the grouping of these ideas can contribute to the health and well-being of individuals affected by this disease. . The information collected was meticulously ordered and direct, with the aim of clarifying possible doubts and uncertainties of the reader. As a complement, online searches were necessary for the construction of this article, which included PUBMED Central, BVS/BIREME, Web of Science, Google Academic, The Cochrane Library and PROSPERO as databases, being carried out through the collected descriptors on the BVS/BIREME platform correspondents with Dislocation; Temporomandibular Joint and Temporomandibular Joint Dysfunction Syndrome. Conclusions: Although TMJ dislocation is the second most common dislocation in the human body, it appears to be an infrequent pathology.